Hasil Supervisi Mutu Pendidikan pada Sekolah Model SMK Negeri 1 Pujut Tahun 2020 - H Jayadi Putra (Universitas Pendidikan Mandalika, 2021)
This study aims to provide assistance to improve quality in accordance with national education standards or to exceed national education standards so that the formation of a quality culture in SMK Negeri 1 Pujut. This research was conducted using descriptive methods. The stages in the implementation of quality supervision, namely; (1) Mapping and validating school conditions, (2) Formulating future recommendations for solutions, (3) Assisting in implementing solutions, and (4) Evaluating their impacts and changes. The data analysis technique of this research is using descriptive analysis. The results of this study include; (1) The understanding of the quality standards at SMKN 1 Pujut is already good, indicated by the quality report cards that have reached SNP 4 with an achievement value of 5.74; (2) Implementation of the Internal Quality Assurance System (SPMI) at SMKN 1 Pujut has been carried out well, starting from quality mapping, planning, implementation, evaluation and standard setting; (3) Implementation of K13 at SMKN 1 Pujut is in accordance with the provisions; (4) Strengthening Character Education (PPK) at SMKN 1 Pujut has been running well, indicated by the results of PPK report cards reaching 6.48 towards SNP 4; (5) The School Literacy Movement (GLS) at SMKN 1 Pujut has achieved SNP with a score of 6.69; and (6) Implementation of UKS at SMKN 1 Pujut reaches 5.8 towards SNP 4.